Stone carving of the Hospitaller period in Rhodes : displaced pieces and fragments - Kasdagli, Anna-Maria (Archaeopress archaeology., 2016)
This work presents 230 stone carvings of the Hospitaller period in Rhodes (1309-1522), which for various reasons are no longer in their original setting.